Multistage Rectal Polypectomy: An Alternative to Proctectomy in Patients With Familial Adenomatous Polyposis. Issue 7 (July 2021) - Sommovilla, Joshua; Liska, David; Church, James
Abstract : INTRODUCTION: When patients with familial adenomatous polyposis have a severely affected rectum, it is usually assumed that endoscopic control is impossible or unwise. The standard approach is proctectomy with either an end ileostomy or an IPAA. Here we show that application of aggressive, multistage snare polypectomy to this situation can be effective and allow the patient to avoid surgery, at least in the short term. TECHNIQUE: Standard polypectomy using snare excision with coagulation is used, taking 2 or 3 sessions, and beginning with the largest polyps. The procedures are performed with the patient under general anesthesia. Endoscopic mucosal resection technique with fluid injection to lift polyps is not necessary. RESULTS: Complete control of the rectal polyps, sustained for at least 2 years, is possible without functional sequelas. CONCLUSIONS: Patients with familial adenomatous polyposis with severe rectal polyposis can be offered multistage rectal polypectomy and safely avoid proctectomy.